Tapas Spanish design for food - Capella, Juli (Accion Cultural Española (AC/E), 2015)
The aim of this book is to show the most recent Spanish creativity in the field of design as applied to fine eating. It is not about food as such, but about the material culture that makes eating possible, that is to say, about the designs that assist and exalt the act of eating. It is called TAPAS in reference to the Spanish custom of the tapa, a little snack of which there are may varieties. And that is how the book is organized too, like a menu with a lot of varied morsels reflecting the topics covered where design plays a relevant role, including the utensils used for cooking, tableware and complementary items and the design of the food itself. Also included is a sample of the graphic design applied to wine labels. A veritable display of imagination that is revolutionizing conventional wine-labeling. The book also traces innovative interior design and decoration as applied to restaurants as well as providing and architectural viewpoint through the wineries that have been built for large Spanish wine producers by prestigious architects. Finally, there is a brief article by two outstanding and internationally renowned creative spirits, Antoni Miralda, artist and pioneering performer in the nexus between art and food, and Marti Guixe, former designer and pioneer of food design.